2020
DOI: 10.13106/jafeb.2020.vol7.no6.255
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Adoption of Industry 4.0 by Small- and Medium-Sized Enterprises: A Case in Ho Chi Minh City, Vietnam

Abstract: The fourth industrial revolution has attracted much academic attention in these past few years. However, research on systematic and extensive factors affecting adoption of Industry 4.0 by SMEs in developing countries, especially in Vietnam, has been unavailable. This study aims to explore the impact of factors that influence the actual adoption of Industry 4.0 by SMEs in Ho Chi Minh City. Mixed-method research was utilized in this study including in-depth interviews of 12 participants and quantitative research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
6
33
0
1
Order By: Relevance
“…The results show that the TAM dimension is proven to have a positive and significant influence on the employee's intention to use SIKEU. The results of this study support the results of previous studies that indicate the intention to use is significantly influenced by the perceived usefulness (Ahmed & Akhlaq, 2015;Byun, 2018;Camilleri & Camilleri, 2019;; O. T. Nguyen, 2020; X. T. Nguyen & Luu, 2020;Park & Kwon, 2016) and the perceived of ease of use (Ahmed & Akhlaq, 2015;Martono et al, 2020;X. T. Nguyen & Luu, 2020).…”
Section: Understanding the Employee's Intention To Use Sikeu Using Tamsupporting
confidence: 90%
“…The results show that the TAM dimension is proven to have a positive and significant influence on the employee's intention to use SIKEU. The results of this study support the results of previous studies that indicate the intention to use is significantly influenced by the perceived usefulness (Ahmed & Akhlaq, 2015;Byun, 2018;Camilleri & Camilleri, 2019;; O. T. Nguyen, 2020; X. T. Nguyen & Luu, 2020;Park & Kwon, 2016) and the perceived of ease of use (Ahmed & Akhlaq, 2015;Martono et al, 2020;X. T. Nguyen & Luu, 2020).…”
Section: Understanding the Employee's Intention To Use Sikeu Using Tamsupporting
confidence: 90%
“…Likewise, if WPs feel that e-Filing is easy to use, then the level of intention to it is also increasing. A system can be said to be quality if it is designed to meet user satisfaction through the ease in using it; it is not only the ease to learn and use the system, but it also the ease of doing a job or task, where users will find it easier to work using the system than do it manually (Aryani et al, 2018;Le, Ngo, Trinh, & Nguyen, 2020;Nguyen, 2020;Nguyen & Luu, 2020;Phan, Nguyen, & Bui, 2019). The ease, in this case, is not only limited to the ease of using e-Filing, but also related to whether this system eases them in completing SPT filling compared to doing it traditionally.…”
Section: Perceived Ease Toward Intention To Use E-filingmentioning
confidence: 99%
“…Someone's positive or negative attitude on cellphone use is based on their valuation of the usability and ease of use (Nguyen & Luu, 2020;Taylor & Todd, 1995). Previous studies had shown that there is a significant and positive influence between perceived ease of use and perceived usefulness (Chtourou & Souiden, 2010;Pai & Huang, 2011;Maier, Laumer, & Weitzel, 2013;Son et al, 2012;Mariani, Curcuruto, & Gaetani, 2013).…”
Section: H5: Social Influence Affects Usefulnessmentioning
confidence: 99%